PERSIAPAN PERANCANGAN SISTEM RAIN WATER HARVESTING (RWH) DI DESA BANYU URIP, KECAMATAN TANJUNG LAGO, KABUPATEN BANYUASIN SEBAGAI UPAYA PENYIMPANAN CADANGAN AIR BERSIH PADA MUSIM KEMARAU - Egi Satria; Anggi Purnama Sari Dewi (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
This study discusses the implementation of a Rain Water Harvesting (RWH) system as a solution for providing clean water reserves in Banyu Urip Village, Tanjung Lago Subdistrict, Banyuasin Regency, particularly during the dry season. Banyu Urip Village faces a clean water crisis during the dry season due to the poor quality of peat water. This activity involved designing and implementing a simple household-based RWH system. As a result, the system was able to collect up to 600 liters of rainwater during a single heavy rainfall, which was then used by residents for daily needs. The program also raised community awareness of the importance of water conservation. Keywords: Rain Water Harvesting (RWH), Clean Water, Dry Season, Water Life Village, Water Conservation